Inside the primary classroom : 20 years on - Galton, Maurice, 1937- (Taylor & Francis, 1999)
This book presents the findings of the second round of research, replicating the original ORACLE study, and documents the changes - or lack of them - in primary education and teaching practice over the last twenty years.